Insurgent Testimonies - Rizzuto, Nicole (Fordham University Press, 2016)
During the second half of the nineteenth century and the first half of the twentieth, insurgencies erupted in imperial states and colonies around the world, including Britain's. As Nicole Rizzuto shows, the writings of Ukrainian-born Joseph Conrad, Anglo-Irish Rebecca West, Jamaicans H. G. de Lisser and V. S. Reid, and Kenyan Ng gi wa Thiong'o testify to contested events in colonial modernity in ways that question premises underlying approaches in trauma and memory studies and invite us to reassess divisions and classifications in literary studies that generate such categories as modernist, colonial, postcolonial, national, and world literatures. Departing from tenets of modernist studies and from methods in the field of trauma and memory studies, Rizzuto contends that acute as well as chronic disruptions to imperial and national power and the legal and extra-legal responses they inspired shape the formal practices of literatures from the modernist, colonial, and postcolonial periods. This title was made Open Access by libraries from around the world through Knowledge Unlatched.